2010
DOI: 10.1007/s11916-010-0106-x
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Cerebral Vasospasm, Multilobular Intracerebral Hemorrhages, and Nonaneurysmal Subarachnoid Hemorrhage: Review of Possible Interrelationships

Abstract: "Reversible cerebral vasoconstriction syndrome" (RCVS) is a recently described entity that is mainly characterized by the association of severe ("thunderclap") headaches with or without additional neurological symptoms and diffuse, multifocal, segmental narrowings involving large and medium-sized cerebral arteries. By definition, angiographic abnormalities disappear within 3 months. The clinical course is usually benign, with a higher prevalence in young women. RCVS is idiopathic in the majority of the cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…However, the localized subarachnoid blood in the right frontal lesion in this patient was clearly remote from the left IC aneurysm. Moreover, it appears extremely unlikely that small localized bleeding at the surface of the brain could explain the subsequent diffuse vasoconstriction in this patient (29). It has been considered that cSAH in RCVS is due to the rupture of small pial vessels caused by a sudden increase in blood pressure, combined with the failure of cerebrovascular autoregulatory mechanisms (30).…”
Section: Discussionmentioning
confidence: 87%
“…However, the localized subarachnoid blood in the right frontal lesion in this patient was clearly remote from the left IC aneurysm. Moreover, it appears extremely unlikely that small localized bleeding at the surface of the brain could explain the subsequent diffuse vasoconstriction in this patient (29). It has been considered that cSAH in RCVS is due to the rupture of small pial vessels caused by a sudden increase in blood pressure, combined with the failure of cerebrovascular autoregulatory mechanisms (30).…”
Section: Discussionmentioning
confidence: 87%
“…Some authors reported that the most important factors influencing outcome are related to complications of intraparenchymal hemorrhage 11 , 13 , 19) . Pathophysiologically, there are multiple factors causing hemorrhages including pial vessel rupture or reperfusion injuries due to high pressure in the narrowed vessels (caused by a sudden increase in blood pressure) combined with impairment of cerebral autoregulation 10 , 16) . However, ischemic complication is developed by involvement of more proximal medium- or large-sized arteries after distal small-sized arteries are affected.…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of RCVS as a cause of spontaneous, non-traumatic SAH may be confused for aneurysmal SAH related vasospasm or primary angiitis of central nervous system (PACNS). In RCVS, associated vasospasm may be distinguished from SAH related vasospasm : absence of ruptured aneurysm; disproportionate distribution related to focal blood clot; segmental vasoconstriction occurring earlier (<4 days); prolonged, but reversible aspect of angiographic vasoconstriction 3 , 4 , 9 , 10) . Although the proximal cisternal segments are mainly affected in SAH related vasospasm, vascular involvement of RCVS started at small distal arteries progressing to medium- and large-sized arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Aufgrund der wiederholt beschriebenen Vasospasmen bei Patienten mit akuten Kopfschmerzen ohne SAB wurde der Begriff des reversiblen zerebralen Vasokonstriktionssyndroms (RCVS) geprägt [17,18]. Dabei können vergleichbar zu einer SAB schwerste plötzliche Kopfschmerzen und fokale Defizite auftreten.…”
Section: Reversibles Zerebrales Vasokonstriktionssyndromunclassified